2007
DOI: 10.1017/s0950268807008382
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of high-risk human papillomavirus (HPV) infection and cervical cytological abnormalities in imprisoned women

Abstract: The aim of the study was to estimate the prevalence and risk factors associated with infection by high-risk human papillomavirus (HR-HPV) in cervix and squamous intra-epithelial lesions (SIL) in imprisoned women. This was done by a cross-sectional study of imprisoned women attending the gynaecological clinic in Foncalent prison in Alicante, Spain. The study period was from May 2003 to December 2005. HR-HPV infection was determined through Digene HPV Test, Hybrid Capture II (HC-II). HPV typing was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
3
18
0
3
Order By: Relevance
“…In our report, a prevalence of 20.7% has been observed, similar to the one reported in Brazil (21.1%) but lower than in other studies [10][11][12][13] . It is certain that women infected by the human immunodeficiency virus are more vulnerable to HPV infection and a high prevalence for the later has been reported in this population group 19,20 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our report, a prevalence of 20.7% has been observed, similar to the one reported in Brazil (21.1%) but lower than in other studies [10][11][12][13] . It is certain that women infected by the human immunodeficiency virus are more vulnerable to HPV infection and a high prevalence for the later has been reported in this population group 19,20 .…”
Section: Discussionsupporting
confidence: 87%
“…Few studies have approached the problem of HPV infection among imprisoned women, with a reported prevalence ranging between 20.1% and 46% depending on the population under study [10][11][12][13] . In Mexico, there is no epidemiologic data on HPV among imprisoned women hence; this study intends to describe the epidemiology of the HPV infection in women deprived of freedom in the state of Yucatan, Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Wright showed the presence of HPV in 73.8% of women aged 25 years with cytological results: ASCUS (p=0.002) [25], while Allen in his study found HPV infection in 94.9% of patients with ASCUS [26]. González has shown that HPV infection five-fold increases the risk of intraepithelial neoplasia [27]. A similar association is shown in other studies [28,29].…”
Section: Discussionsupporting
confidence: 56%
“…In einer Studie, in der 866 weibliche Insassen über Tabakkonsum befragt wurden, berichteten 12,5% (von den 619 Raucherinnen) über Tabakinduzierte medizinische Probleme (keine genaue Angabe über die Art des Problems) (Cropsey, Eldridge et al 2004). Eine Prävalenz-Studie über chronische Erkrankungen aus den USA zeigt, dass Häftlinge und Gefangene signifikant öfter an Bluthochdruck, Diabetes, Herzinfarkt, Asthma, Arthritis, Gebärmutterhalskrebs und Hepatitis leiden als nicht-institutionalisierte Er-wachsene (Binswanger, Krueger et al 2009 (Gonzalez, Canals et al 2008).…”
Section: Tabakrauchen Und Gesundheitunclassified